Ārāmgāhʹhā-yi junūb-i gharb-i Īrān: khūzistān va manāṭiq-i hamjavār = The tombs buildings the South Western Iran : (Khuzestan and the neighboring areas) - Sajjādī, ʻAlī (Pizhūhishgāh-i Mīrās̲-i Farhangī va Gardishgarī, Markaz-i Muʻarrifī-i Farhangī, 2017)
Islamic architecture - Iran - Khūzistān ; Tombs - Iran - Khūzistān ; Islamic architecture - Iran - Luristān ; Tombs - Iran - Luristān